A case study concerning the 5S lean technique in a scientific equipment manufacturing company. Issue 3 (10th April 2020) - Gupta, Shaman; Chandna, Pankaj
Abstract : Purpose: This paper's purpose is to help a scientific equipment company make use of the 5S tool on the shop floor so that the organization can become progressively beneficial and increasingly productive. Design/methodology/approach: The organization has adopted a simple approach for making a suitable team for 5S tool implementation at the workplace. After that, they have used three types of data-collection methods so that these methods could help in the correct introduction of the 5S tool in the business workplace. They have also analysed the regression analysis with the genetic algorithm for the audit scores to predict the behaviour of 5S implementation in the coming weeks. Findings: In this case study, it has been found after the suitable analysis that the 5S tool implementation has resulted in the overall benefits of the workplace. The major benefit achieved with the 5S tool is that the searching time for the tool in the workplace has been improved significantly. Also, the safety level is increased. The 5S audit has been carried out in the workplace and the audit score has been improved from the level of 6 scores (in week 1) to 72 score (in week 24). Practical implications: 5S tool has emerged as an incredible asset and it tends to be actualized in any of the ventures whether it is of a miniature, small, medium or large scale industry. The 5S tool can be applied horizontally at a large scale and it can be applied to almost all the workstations in the workplace. Originality/value: The presented productions and contextual investigation for the 5S tool will be helpful and useful for all the analysts, experts and all other people who are worried about this subject of the 5S tool and its implementation in the organization.